# GSEB Solutions Class 8 Maths Chapter 14 Factorization Ex 14.4

Gujarat BoardĀ GSEB Textbook Solutions Class 8 Maths Chapter 14 Factorization Ex 14.4 Textbook Questions and Answers.

## Gujarat Board Textbook Solutions Class 8 Maths Chapter 14 Factorization Ex 14.4

Question 1.
Find and correct the errors in the following mathematical statements?
1. 4(x – 5) = 4x – 5
2. x(3x + 2) = 3x2 + 2
3. 2x + 3y = 5xy
4. x + 2x + 3x = 5x
5. 5y + 2y + y – 7y = 0
6. 3x + 2x = 5x2
7. (2x)2 + 4(2x) + 7 = 2x2 + 8x + 7
8. (2x)2 + 5x = 4x + 5x = 9x2
9. (3x + 2)2 = 3x2 + 6x + 4
10. Substituting x = -3 in
(a) x2 + 5x + 4 gives (-3)2 + 5(-3) + 4
= 9 + 2 + 4 = 15

(b) x2 – 5x + 4 gives (-3)2 – 5(-3) + 4
= 9 – 15 + 4 = – 2

(c) x2 + 5x gives (-3)2 + 5(-3)
= – 9 – 15 = -24

11. (y – 3)2 = y2 – 9
12. (z + 5)2 = z2 + 25
13. (2a + 3b)(a – b) = 2a2 – 3b2
14. (a + 4)(a + 2) = a2 + 8
15. (a – 4)(a – 2) = a2 – 8
16. $$\frac{3 x^{2}}{3 x^{2}}$$
17. $$\frac{3 x^{2}+1}{3 x^{2}}$$
18. $$\frac{3x}{3x+2}$$ = $$\frac{1}{2}$$
19. $$\frac{3}{4x+3}$$ = $$\frac{1}{4x}$$
20. $$\frac{4x+5}{4x}$$ = 5
21. $$\frac{7x+5}{5}$$ = 7x
Solution:
1. 4(x – 5) = 4x – 5
The given statement is incorrect.
The correct statement is:
4(x – 5) = 4x – 20 (āµ4 Ć 5 = 20)

2. x(3x + 2) = 3x2 + 2
It is an incorrect statement.
The correct statement is:
x(3x + 2) = 3x2 + 2x

3. 2x + 3y = 5xy
It is an incorrect statement.
The correct statement is:
2x + 3y = 2x + 3y

4. x + 2x + 3x = 5x
āµ 1 + 2 + 3 = 5 is an incorrect statement.
ā“ The correct statement is:
x + 2x + 3x = 6x

5. 5y + 2y + y – 7y = 0
It is an incorrect statement,
āµ 5y + 2y + y = 8y and 8y – 7y = y
ā“ The correct statement is 5y + 2y + y – 7y = y

6. 3x + 2x = 5x2
It is an incorrect statement.
The correct statement is:
3x + 2x = 5x

7. (2x)2 + 4(2x) + 7 = 2x2 + 8x + 7
āµ (2x)2 = 4x2
The given statement is incorrect.
The correct statement is:
(2x)2 + 4(2x) + 1 = 4x2 + 8x + 7

8. (2x)2 + 5x = 4x + 5x = 9x, is an incorrect statement.
āµ (2x)2 = 4x2
ā“ The correct statement is:
(2x)2 + 5x = 4x2 + 5x

9. (3x + 2)2 = 3x2 + 6x + 4
The given statement is incorrect.
āµ (3x + 2)2 = (3x)2 + 2(3x)(2) + (2)2
= 9x2 + 12x + 4
ā“ The correct statement is:
(3x + 2)2 = 9x2 + 12x + 4

10. (a) Incorrect statement.
āµ x2 + 5x + 4 = (-3)2 + 5(-3) + 4
= 9 – 15 + 4
= (9 + 4) – 15
= 13 – 15 = – 2
Thus, the correct statement is:
x2 + 5x + 4 = (-3)2 + 5(-3) + 4
= 9 – 15 + 4 = -2

(b) We have
x2 – 5x + 4 = (-3)2 – 5(-3) + 4
= 9 + 15 + 4 = 28
ā“ The correct statement is:
x2 – 5x + 4 at x = -3 is
(-3)2 – 5(-3) + 4 = 9 + 15 + 4 = 28

(c) āµ x2 + 5x at x = -3 is
(-3)2 + 5(-3) = 9 – 15 = -6
ā“ The correct statement is:
x2 + 5x at x = -3 is
(-3)2 + 5(-3) = 9 – 15 = -6

11. (y – 3)2 = y2 – 9
The given statement is incorrect
āµ (y – 3)2 = y2 – 2(y)(3) + (3)2
= y2 – 6y + 9
The correct statement is
(y – 3)2 = y2 – 6y + 9

12. (z + 5)2 = z2 + 25
The given statement is incorrect
āµ (z + 5)2 = z2 + 2(z)(5) + (5)2
= z2 + 10z + 25

13. (2a + 3b)(a – b) = 2a2 – 3b2
āµ (2a + 3b) (a – b)
= a(2a + 3b) – b(2a + 3b)
= 2a2 + 3ab – 2ab – 3b2 = 2a2 + ab – 3b2
ā“ The correct statement is:
(2a + 3b)(a – b) = 2a2 + ab – 3b2

14. (a + 4)(a + 2) = a2 + 8
Since (a + 4) (a + 2)
= a(a + 4) + 2 (a + 4)
= a2 + 4a + 2a + 8 = a2 + 6a + 8

15. (b – 4)(a – 2) = a2 – 8
Since(a – 4) (a – 2) = a(a – 2) – 4(a – 2)
= a2 – 2a – 4a + 8 = a2 – 6a + 8
ā“ The correct statement is:
(a – 4)(a – 2) = a2 – 6a + 8

16. $$\frac{3 x^{2}}{3 x^{2}}$$ = 0
It is an incorrect statement
āµ The correct statement is
$$\frac{3 x^{2}}{3 x^{2}}$$ = 1

17. $$\frac{3 x^{2}+1}{3 x^{2}}$$ = 1 + 1 = 2
Since $$\frac{3 x^{2}+1}{3 x^{2}}=\frac{3 x^{2}}{3 x^{2}}+\frac{1}{3 x^{2}}$$
= 1 + $$\frac{1}{3 x^{2}}$$
ā“ The correct statement is:
$$\frac{3 x^{2}+1}{3 x^{2}}=1+\frac{1}{3 x^{2}}$$

18. $$\frac{3}{3x+2}$$ = $$\frac{1}{2}$$
The given statement is incorrect.
The correct statement is
$$\frac{3x}{3x+2}$$ = $$\frac{3x}{3x+2}$$

19. $$\frac{3}{4x+3}$$ = $$\frac{1}{4x}$$
The given statement is incorrect
The correct statement is
$$\frac{3}{4x+3}$$ = $$\frac{3}{4x+3}$$

20. $$\frac{4x+5}{4x}$$ = 5
āµ $$\frac{4x+5}{4x}$$ = $$\frac{4x}{4x}$$ + $$\frac{5}{4x}$$ = 1 + $$\frac{5}{4x}$$
ā“ The correct statement is:
$$\frac{7x+5}{5}$$ = $$\frac{7x}{5}$$ + 1